The role of non-timber forest products in conservation and development - Arnold, J.E.M.; Ruíz Pérez, M. (1998)
This paper discusses the assumptions underlying non-timber forest product (NTFP)-based approaches. The authors examine conservation dimensions, highlighting the differences in perceptions among different stakeholder groups about what should be conserved, and development issues, including the role of NTFPs in meeting cultural and subsistence, and in enabling people to deal with increasing integration into market systems. This is followed by an examination of the institutional frameworks that influence pursuit of both conservation and development objectives. It is suggested that more attention should be given to understanding the limitations on NTFP conservation and development, including the effects of market fluctuations and the tendency for many NTFPs to encounter boom-bust cycles. The evaluation of income generation options for forest dwellers should consider not only NTFPs but also other products, enterprises or employment opportunities. It concludes that there is a need to analyse NTFP initiatives on a case-by-case basis because of the variable conservation or development potential associated with non-timber forest products.